2019
DOI: 10.1093/mnrasl/slz086
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of weak coherent pulsations in the ultraluminous X-ray source NGC 1313 X-2

Abstract: We report the detection of weak pulsations from the archetypal ultraluminous X-ray source (ULX) NGC 1313 X-2. Acceleration searches reveal sinusoidal pulsations in segments of two out of six new deep observations of this object, with a period of ∼ 1.5 s and a pulsed fraction of ∼ 5%. We use Monte Carlo simulations to demonstrate that the individual detections are unlikely to originate in false Poisson noise detections given their very close frequencies; their strong similarity to other pulsations detected from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 33 publications
(47 reference statements)
3
136
1
Order By: Relevance
“…Although the PFs are treated as constant in time in the present study, the time variation of the PF and the intermittent signal has been recently reported by Rodríguez Castillo et al (2019) and Sathyaprakash et al (2019). The time variation of the PF might be explained by the vari-ation of the mass accretion rate.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the PFs are treated as constant in time in the present study, the time variation of the PF and the intermittent signal has been recently reported by Rodríguez Castillo et al (2019) and Sathyaprakash et al (2019). The time variation of the PF might be explained by the vari-ation of the mass accretion rate.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
“…Our results are consistent with the observations of ULXPs with few exception mentioned in the next para-graph. The PF of M82 X-2, NGC7793 P13, NGC5907 ULX, NGC1313 X-2, and M51 ULX7 was reported to be about 5-25 % at 3-30 keV (Bachetti et al 2014), 8-40 % at 1-15 keV (Fürst et al 2016;Israel et al 2017b), 12-20 % at 2.5-7 keV (Israel et al 2017a), 3-8 % at 0.3-10 keV (Sathyaprakash et al 2019) and 5-40 % at 0.3-9 keV (Rodríguez Castillo et al 2019), respectively. NGC300 ULX1 exhibits the PF of ≤ 50 % at the energy band of < ∼ 1 keV (Carpano et al 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…The orbital period of NGC 300 ULX-1 is unknown. Contrary to other ULX pulsars, whose orbital periods have been determined or constrained from Doppler shifts of the pulse period (Bachetti et al 2014;Israel et al 2017;Fürst et al 2018;Sathyaprakash et al 2019;Rodríguez Castillo et al 2019), the pulse period evolution of NGC 300 ULX-1 shows no sign of orbital modulations (Ray et al 2018;Vasilopoulos et al 2018). This is due in part to the very high absolute spin-up rate, which makes it difficult to detect small modulations to the spin period due to orbital motions.…”
Section: Orbital Parametersmentioning
confidence: 96%
“…The timescale for photons to escape the medium (t sc ) is set by the electron mean free path l sc = 1/σ T n e and number of scatterings n, such that t sc = n(l sc /c). Given that the number of scatterings scales roughly as the square of the optical depth (Rybicki & Lightman 1979), we can rewrite the timescale for Compton scattering as t sc = σ T n e R 2 sp /c.…”
Section: The Origin Of the Lagmentioning
confidence: 99%